GENERIC PROGRAMMING IN C++, USING METAPROGRAMMING - Raffo Lecca, Eduardo (2007)
The complexity in our programs increases along with the problems we deal with. A way of solving them is to repeat more than once the same structures, just like traditional or imperative programming accustomed us to. This article explores the relationships among C++ templates, generic programming and the ability to develop statistics computations and generation of codes. Several developers use languages of high level to developers use languages of high level to develop applications in scientific computation; and the mechanism of templates in C++ allows them to solve important problems in the design of libraries of class.